Pollution Caused by Humans: A Curse on Animals - Gupta, Sanchi; Gupta, Sanchi; Tomar, Aakarsh (International Journal of Environment, Agriculture and Biotechnology, 2019)
The study explores the pervasiveness and causes of Pollution causing detrimental impact on health conditions of animals finally leading to increase in the death ratio of animals in the country. Pollution can be of various types such as Air pollution, Noise Pollution, Water Pollution and so on. These types of Pollution are caused due to the release of Hazardous Chemicals in our environment and by the improper activities done by the human beings in the society. On the contrary a complete on Pollution within the country would not be possible, but a conscious effort needs to be there to save our Country and its human beings and animal species. Already there has been a huge increase in the death Ratio of animals in the country from past decades. There are various ways in which Pollution within the Country can be managed and reduced such as walking smaller distances than using vehicles causing pollution, not throwing garbage particles in the water bodies, eating plant based diet and not slaughtering animals(which is major cause of pollution in environment). This research paper tends to strike the drastic damage caused to life of animals due to pollution by taking some universal essentials and also show their preclusion.